Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To reduce the expression [tex]\((3 - i)(4 + 5i)(6 + 2i)\)[/tex] into the form [tex]\(a + bi\)[/tex], follow these steps:
1. Multiply [tex]\((3 - i)\)[/tex] and [tex]\((4 + 5i)\)[/tex] first:
Let's denote:
[tex]\[ z_1 = 3 - i \][/tex]
[tex]\[ z_2 = 4 + 5i \][/tex]
Calculate [tex]\(z_1 \cdot z_2\)[/tex]:
[tex]\[ (3 - i)(4 + 5i) = 3 \cdot 4 + 3 \cdot 5i - i \cdot 4 - i \cdot 5i \][/tex]
Simplify step-by-step:
[tex]\[ = 12 + 15i - 4i - 5i^2 \][/tex]
Recall that [tex]\(i^2 = -1\)[/tex], so:
[tex]\[ = 12 + 15i - 4i + 5 \][/tex]
Combine like terms:
[tex]\[ = (12 + 5) + (15i - 4i) \][/tex]
[tex]\[ = 17 + 11i \][/tex]
2. Now multiply the result [tex]\((17 + 11i)\)[/tex] with [tex]\((6 + 2i)\)[/tex]:
Let’s denote:
[tex]\[ z_3 = 6 + 2i \][/tex]
Calculate [tex]\((17 + 11i) \cdot (6 + 2i)\)[/tex]:
[tex]\[ (17 + 11i)(6 + 2i) = 17 \cdot 6 + 17 \cdot 2i + 11i \cdot 6 + 11i \cdot 2i \][/tex]
Simplify step-by-step:
[tex]\[ = 102 + 34i + 66i + 22i^2 \][/tex]
Recall that [tex]\(i^2 = -1\)[/tex], so:
[tex]\[ = 102 + 34i + 66i + 22(-1) \][/tex]
[tex]\[ = 102 + 100i - 22 \][/tex]
Combine like terms:
[tex]\[ = (102 - 22) + 100i \][/tex]
[tex]\[ = 80 + 100i \][/tex]
So, the result in the form [tex]\(a + bi\)[/tex] is:
[tex]\[ 80 + 100i \][/tex]
Therefore, [tex]\(a = 80\)[/tex] and [tex]\(b = 100\)[/tex].
1. Multiply [tex]\((3 - i)\)[/tex] and [tex]\((4 + 5i)\)[/tex] first:
Let's denote:
[tex]\[ z_1 = 3 - i \][/tex]
[tex]\[ z_2 = 4 + 5i \][/tex]
Calculate [tex]\(z_1 \cdot z_2\)[/tex]:
[tex]\[ (3 - i)(4 + 5i) = 3 \cdot 4 + 3 \cdot 5i - i \cdot 4 - i \cdot 5i \][/tex]
Simplify step-by-step:
[tex]\[ = 12 + 15i - 4i - 5i^2 \][/tex]
Recall that [tex]\(i^2 = -1\)[/tex], so:
[tex]\[ = 12 + 15i - 4i + 5 \][/tex]
Combine like terms:
[tex]\[ = (12 + 5) + (15i - 4i) \][/tex]
[tex]\[ = 17 + 11i \][/tex]
2. Now multiply the result [tex]\((17 + 11i)\)[/tex] with [tex]\((6 + 2i)\)[/tex]:
Let’s denote:
[tex]\[ z_3 = 6 + 2i \][/tex]
Calculate [tex]\((17 + 11i) \cdot (6 + 2i)\)[/tex]:
[tex]\[ (17 + 11i)(6 + 2i) = 17 \cdot 6 + 17 \cdot 2i + 11i \cdot 6 + 11i \cdot 2i \][/tex]
Simplify step-by-step:
[tex]\[ = 102 + 34i + 66i + 22i^2 \][/tex]
Recall that [tex]\(i^2 = -1\)[/tex], so:
[tex]\[ = 102 + 34i + 66i + 22(-1) \][/tex]
[tex]\[ = 102 + 100i - 22 \][/tex]
Combine like terms:
[tex]\[ = (102 - 22) + 100i \][/tex]
[tex]\[ = 80 + 100i \][/tex]
So, the result in the form [tex]\(a + bi\)[/tex] is:
[tex]\[ 80 + 100i \][/tex]
Therefore, [tex]\(a = 80\)[/tex] and [tex]\(b = 100\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.